2006
DOI: 10.1210/jc.2006-1516
|View full text |Cite
|
Sign up to set email alerts
|

School-Based Intervention Acutely Improves Insulin Sensitivity and Decreases Inflammatory Markers and Body Fatness in Junior High School Students

Abstract: Short-term school-based health, nutrition, and exercise intervention is beneficial to all students and affects multiple diabetes risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
112
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(118 citation statements)
references
References 19 publications
3
112
2
1
Order By: Relevance
“…The adiponectin was significantly decreased in the SIA. However, consistent with the previous intervention studies in children (Chae et al, 2010;Rosenbaum et al, 2007), the changes in adiponectin in the current study did not differ between groups. In contrast, a study in obese adolescents showed increased adiponectin after a 3-month lifestyle intervention (physical activity, caloric restriction and limiting TV time) (Balagopal et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The adiponectin was significantly decreased in the SIA. However, consistent with the previous intervention studies in children (Chae et al, 2010;Rosenbaum et al, 2007), the changes in adiponectin in the current study did not differ between groups. In contrast, a study in obese adolescents showed increased adiponectin after a 3-month lifestyle intervention (physical activity, caloric restriction and limiting TV time) (Balagopal et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…For example, Chae et al (2010) found that CRP and body weight were decreased in obese children after a 12-week structured exercise program including nutritional education. Rosenbaum et al (2007) reported that a 3 to 4-month school-based intervention program (aerobic exercise and health education classes) significantly reduced body fatness and CRP in children. We extended the existing knowledge by examining the effects over one-year period of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, conclusions regarding efficacy of schoolbased obesity prevention programs are limited [9]. Although some school-based interventions have reported effects on overweight or obesity [10][11][12], most, particularly those involving large cohorts [13,14], have not [15], and several short-term, school-based programs had little effect on BMI [16,17]. Schoolbased prevention programs have been shown to be feasible, acceptable, and desirable for improving students' health status [18], and improving school-related behavior [19].…”
mentioning
confidence: 99%
“…food service at schools Results: Repeated measures between 1994 and 2002 showed increases in BMI and skinfolds; PA, fitness and TV watching showed improvements by 1999 but these improvements were not maintained by 2002; key high-fat high-sugar foods decreased but so did fruit and vegetables Conclusion: Long-term results disappointing NEEMA* (18,73) Fifty-eight children, 4th grade from six schools, > 40% African-American enrolment Design: pretest and post test, single sample design, 7 weeks Aim: the objectives were to decrease dietary saturated fat intake, increase fibre intake and increase PA in African-American children; regarded as pilot study for African-Americans Intervention: health class and physical education curriculum sessions, school cafeteria intervention, family programme, after-school health club; based on social cognitive and social ecological theory and culturally adapted Results: Fitness laps increased, fasting capillary glucose and percentage body fat decreased Conclusion: The NEEMA pilot study provided teacher feedback useful for revising the NEEMA health curricula and positive preliminary impact of the PA class on children's fitness and blood glucose levels Zuni Pueblo of New Mexico (45) Seventy-two Zuni pupils, thirty-seven Anglo pupils (English-speaking Caucasians), two high schools, native American youth Design: multiyear cross-sectional evaluation of 4 years, comparison of Zunis with Anglos Aim: To change behaviours known to influence DM risk, i.e. food intake, PA and knowledge of DM Intervention: development of a youth fitness centre with equipment and instructors at the school; school food service improved healthy foods available and water cooler bottles replaced sugared soft drinks; DM prevention was addressed by the school curriculum Results: Plasma glucose values normal at baseline and no differences between Zuni and Anglos; fasting and 30 min insulin were significantly higher in Zuni at baseline but decreased; at 3 years males (only) values were same as Anglos Conclusion: intervention can improve insulin levels Junior high school (20) Seventy-three children (forty-nine in intervention group, twenty-four in control group), 8th grade, one junior high school, predominantly Hispanic Design: RCT Aim: to evaluate the effects of a 3-4 month intervention of health, nutrition and PA on DM risk Intervention: classroom curriculum of fourteen sessions of 45 min each on nutrition education and PA. Three PA sessions per week Results: reduction in body fatness, insulin resistance and C-reactive protein and IL-6 Conclusion: short-term intervention is beneficial and affects multiple DM risk factors Sandy Lake Diabetes Prevention Programme (15) 122 Ojibway-Cree children; 3-5th grade students from a Native North American reserve in Ontario, Canada Design: pretest and post-test, single sample design, 2 years Aim: focus on knowledge and skill development related to healthy eating, PA and DM education Intervention: mainly a DM prevention curriculum of sixteen weekly 45 min teacher-led sessions; a family and peer component, environment and school meal components; based on social cognitive and social ecological theory and culturally adapted Results: increases in dietary intention, preference, knowledge and self-efficacy and in curriculum knowledge scale after the intervention; % energy from fat decreased in boys; increased exposure to intervention was associated with meeting the fibre recommendation Conclusion: intervention associated with improved knowledge and psycho-social factors related to healthy eating and dietary fibre intake Bienestar (Well-Being)…”
Section: Existing Reviews On Interventions For Diabetes Preventionmentioning
confidence: 99%